A pill for every ill? Unpacking antibiotic misuse among Bangladeshi university students - Abu Hossain Muhammad Ahsan; Maruf Hasan Rumi; Niaz Makhdum (International Journal of Qualitative Studies on Health & Well-Being)
Background The misuse of antibiotics and the resulting emergence of antibiotic resistance in bacterial strains are both important global health issues worldwide, especially for developing countries including Bangladesh. Objective The study investigated the antibiotic-seeking behaviour of Bangladeshi university students and the views of medical and public health experts on the harmful effects of antibiotic overuse on students. Method Forty in-depth students’ interviews and 10 key informant interviews with medical and public health professionals were used to collect data using a qualitative study design and descriptive phenomenology research approach. Thematic analysis technique was conducted to analyse the collected data. Results The study found university students frequently seek, ask for and consume antibiotics from pharmacies to recover quickly and reduce the time-cost-visit of treatment. In certain instances, medical practitioners recommend antibiotics as a general treatment approach to enhance their popularity among patients and expedite their recovery from illness. However, they are being led into protracted illness due to poor knowledge and excessive usage of antibiotics. Conclusion Students risk serious health issues by taking unnecessary antibiotics to recuperate quickly, which increases the nation’s health burden. The study stresses the need for stricter restrictions and limiting antibiotic availability and intervention in educational, community and policy settings.